Penerapan Quality of Service Dalam Menganalisis Kualitas Kinerja Metode Simple Queue Dan Queue Tree - Novita Sari; Febriyanti Panjaitan (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
Abstract Internet use for employees is a necessity to facilitate work so that it can be completed properly. A good internet connection can be seen from the quality provided to its users. Stable internet is certainly a necessity for work activities to run smoothly without any obstacles. Therefore, this study applies Quality of Service (QoS) in analyzing the quality of computer network performance at the Prabumulih Information and Communications Service. the need for analysis using QoS to manage and optimize network quality, this research was carried out based on the stages of the Action Research method and standardization of TIPHON with wireshark application measurement tools. the results obtained from the simple queue method are in the "very good" category and for the queue tree method in the "good" category